Marketing status and perceived efficacy of drugs for supporting abstinence and reducing alcohol intake in alcohol use disorders: a survey among European federation of addiction societies in Europe - Bramness, Jørgen Gustav; Mann, Karl; Wurst, Friedrich Martin (European addiction research, 2016)
Background: Acamprosate, disulfiram (DIS), naltrexone and nalmefene can be used in treating alcohol use disorders. The drugs are, however, underutilized. Methods: In this survey of marketing status and perceived efficacy, member societies of the European federation for addiction societies were asked to report on the status of these drugs in their country. Results were obtained from 20 European countries showing that the drugs were registered in most countries. Results and Conclusion: The drugs were mentioned in guidelines in approximately half and were partially or fully reimbursed in half to two-thirds countries. DIS was perceived as the most efficacious drug. These results are discussed.
Gesehen am 02.07.2019